PERSPEKTIF HUKUM TERHADAP PEREMPUAN SEBAGAI KORBAN TINDAK PIDANA PERDAGANGAN ORANG - Atmaja, I Gusti Bagus Agung Kusuma; Meitridwiastiti, Anak Agung Ayu (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2024)
Human trafficking is currently still a problem that has not been completely solved in Indonesia because human trafficking is a transnational crime. The victims are usually employed as beggars, maids, domestic helpers, pornography and prostitution practices. The government in this case has also regulated the issue of human trafficking through Law Number 21 of 2007 concerning the Eradication of Human Trafficking, as well as in the Criminal Code (KUHP). This crime of human trafficking often makes women as victim. Thus, this must be a big concern from the government and the community to avoid more victims in the future, because human trafficking, in this case women, is a deprivation of women's freedom of life and certainly is not in line with the principles of human rights. Although the laws and regulations clearly regulate and prohibit this human trafficking practice, there are still people who do not care about it and do not seem to be afraid of the sanctions for their actions. The method used in this study is the normative juridical legal research method, namely by using the statutory approach (Statute Approach) and the conceptual approach (Conceptual Approach).